DECENTRALIZATION AND DISASTER COLLABORATIVE MANAGEMENT OF CHINA PAKISTAN ECONOMIC CORRIDOR BASED ON EMOTIONAL BEHAVIOR CHANGE - Wuzhati, Yeerken (The international journal of neuropsychopharmacology, 2022)
Abstract Background Although China Pakistan Economic Corridor (CPEC) plays a key role in China's “the Belt and Road” initiative, the region cannot avoid various disasters. In fact, the China Pakistan Economic Corridor, especially Pakistan, is one of the most vulnerable areas in the world. With CPEC's vision of decentralized disaster governance and response system, we urgently need to promote our new cross-border disaster management. The disasters along CPEC highlight the differences in cross-border health and well-being. In particular, people analyze the emotions and emotional changes in corridor decentralization and disaster collaborative management. Research Objects and Methods This paper systematically analyzes the disasters of China Petroleum Engineering Construction Co., Ltd. and the evolution of its disaster management system. Specifically, this paper compares the disaster management systems and mechanisms of China and Pakistan at the national, provincial, municipal and community levels, and then carefully studies the current trend of decentralized disaster management through a recent round of semi-structured and public interviews in Xinjiang From their experience, the problems and gaps between decentralized and decentralized disaster management have been found. At the same time, this study uses (1) positive emotion scale to analyze the changes of people's emotional behavior in this area. Panas emotion scale developed by Watson et al. It is widely used to measure emotions. The scale includes two dimensions: positive emotion and negative emotion. There are 6 questions in this dimension, which are scored by Likert 5 points: 1 means “very inconsistent”, 5 means “very consistent”, the same below). In this study, the CA coefficient of the questionnaire is 0.90. (2) Motivation scale. The topic of measuring motivation mainly refers to the entrepreneurial motivation scale compiled by Phan, with a total of 8 questions, using Likert 5-point scoring method. (3) Social support scale. The scale is adapted from the social support scale compiled by Ye Yuemei et al. It has 8 questions and is scored by Likert with 5 points. C scale α The coefficient is 0.87. (4) Behavioral propensity scale. Entrepreneurial orientation dimension in intention measurement. The scale has 6 questions and is scored by Likert with 5 points. scale α The C coefficient of is 0.95. Results This paper discusses the latest trend of disaster management along China Pakistan Economic Corridor (CPEC). China and Pakistan have shown a trend of decentralization, but this is still a legacy of the strong role of the state in the disaster policy agenda. Therefore, the case investigation results of CPEC show that national and provincial disaster management institutions play a key role in disaster relief. At the same time, we will vigorously focus on disaster management and highlight the role of municipal governments and communities as key subjects of disaster management. Although the decentralization of disaster management system has become the mainstream trend of China and Pakistan, Xinjiang, China, is vast and sparsely populated, and the fragmentation of administrative management has brought many obstacles to the practice of Multi Center disaster management. Conclusion The results of CPEC case investigation show that national and provincial disaster management institutions have played a key role in disaster relief. At the same time, we will vigorously focus on disaster management and highlight the role of municipal governments and communities as key subjects of disaster management. Although the decentralization of disaster management system has become the mainstream trend of China and Pakistan, Xinjiang, China, is vast and sparsely populated, and the fragmentation of administrative management has brought many obstacles to the practice of Multi Center disaster management. Acknowledgements This study was supported by the National Natural Science Foundation of China [grant number 41701138] and the Strategic Priority Research Program (A) of the Chinese Academy of Sciences [grant numbers XDA20010103].